Risk Factors for Heart Failure: 20-Year Population-Based Trends by Sex, Socioeconomic Status, and Ethnicity - Lawson, Claire A.; Zaccardi, Francesco; Squire, Iain; Okhai, Hajra; Davies, Melanie; Huang, Weiting; Mamas, Mamas; Lam, Carolyn S.P.; Khunti, Kamlesh; Kadam, Umesh T. (Circulation. Heart failure, 2020)
There are multiple risk factors for heart failure, but contemporary temporal trends according to sex, socioeconomic status, and ethnicity are unknown. Using a national UK general practice database linked to hospitalizations (1998-2017), 108 638 incident heart failure patients were identified. Differences in risk factors among patient groups adjusted for sociodemographic factors and age-adjusted temporal trends were investigated using logistic and linear regression. Over time, a 5.3 year (95% CI, 5.2-5.5) age difference between men and women remained. Women had higher blood pressure, body mass index, and cholesterol than men ( <0.0001). Ischemic heart disease prevalence increased for all to 2006 before reducing in women by 0.5% per annum, reaching 42.7% (95% CI, 41.7-43.6), but not in men, remaining at 57.7% (95% CI, 56.9-58.6; interaction =0.002). Diabetes mellitus prevalence increased more in men than in women (interaction <0.0001). Age between the most deprived (74.6 years [95% CI, 74.1-75.1]) and most affluent (79.9 [95% CI, 79.6-80.2]) diverged (interaction <0.0001), generating a 5-year gap. The most deprived had significantly higher annual increases in comorbidity numbers (+0.14 versus +0.11), body mass index (+0.14 versus +0.11 kg/m ), and lower smoking reductions (-1.2% versus -1.7%) than the most affluent. Ethnicity trend differences were insignificant, but South Asians were overall 6 years and the black group 9 years younger than whites. South Asians had more ischemic heart disease (+16.5% [95% CI, 14.3-18.6]), hypertension (+12.5% [95% CI, 10.5-14.3]), and diabetes mellitus (+24.3% [95% CI, 22.0-26.6]), and the black group had more hypertension (+12.3% [95% CI, 9.7-14.8]) and diabetes mellitus (+13.1% [95% CI, 10.1-16.0]) but lower ischemic heart disease (-10.6% [95% CI, -13.6 to -7.6]) than the white group. Population groups show distinct risk factor trend differences, indicating the need for contemporary tailored prevention programs.